A six-years point prevalence survey of healthcare-associated infections in an Italian hospital. (13th November 2019) - Gentili, A; La Milia, D I; Vallone, D; Di Pumpo, M; Vangi, G; Berloco, F; Cambieri, A; Damiani, G; Laurenti, P; Ricciardi, W
Abstract: : Healthcare-Associated Infections (HAIs) are among the most serious public health problems in Europe representing the most frequent adverse event during care delivery. Despite their limitations, point prevalence surveys of HAIs are often preferred to prospective surveillance, since they provide a feasible estimate when resources are limited. The aim of this study was to analyze the results of a six-years point prevalence survey of HAIs in a teaching acute care hospital in Italy and to investigate the main risk factors of HAIs in the acute-care hospital. A point prevalence survey to detect HAIs was carried out in Gemelli Hospital during the last 6 years, from 2013 to 2018. Inpatients of any age in Gemelli Hospital were eligible for inclusion. Patients in outpatient areas were excluded. HAIs were identified according to diagnosis guideline from ECDC in 2011. Statistically significant differences were tested through t-test and Chi-square test. Multi-variate analysis was performed to evaluate the impact of regressor factors for predict HAI's prevalence. The statistical significance level was set at p < 0.05. The point prevalence ranged from 3, 16% in 2017 to 6, 64% in 2013. Pneumonia and surgical site infections (SSI) were the most frequent HAIs during the 6 years, with a rate of 27, 31% and 26, 20% respectively of all HAIs. The multiple logistic regression showed that length of stay at the moment of detection, urinary catheter, CVC and antibiotic therapy are useful to meaningfully predict HAI prevalence, with a regression coefficient (adjusted R2) of 0.2780. Thanks to proper hospital policies, the point prevalence of HAIs does not seem to increase through the years, even though it is still too early to draw any conclusions. Pneumonia and SSI represented each one more than a quarter of all the HAIs, as reported also in literature. There is a strong association between length of stay at the moment of detection and HAIs but it is hard to understand which one is the cause of the other. Key messages: Point prevalence from 2013 to 2018 seems to be stable. An accurate incidence survey is needed in order to identify the main risk factors of HAI and to realize more specific hospital programmes. Length of stay at the moment of detection is useful to meaningfully predict HAIs prevalence although the cause-and-effect relationship is still not clear.